2018
DOI: 10.1080/08916934.2018.1488968
|View full text |Cite
|
Sign up to set email alerts
|

The association of non-alcoholic fatty liver disease with thyroid peroxidase and thyroglobulin antibody: A new insight from SPECT-China study

Abstract: Non-alcoholic fatty liver disease (NAFLD) has been studied with inflammation and immune, but the link with thyroid autoimmunity is unreported. This study aimed to explore the direct association of NAFLD with thyroid autoimmune disease (AITD) among participants with normal thyroid stimulating hormone (TSH) levels. The data were obtained from a cross-sectional study (SPECT-China). A total of 7982 participants were enrolled. Participants underwent several checkups including peroxidase antibody (TPOAb), thyroglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…As can be seen from Table 2, the prevalence of thyroid antibodies positive in the T2DM combined NAFLD group was significantly higher than that in the T2DM group alone, and TPOAb positive are more than TGAb-positive patients, the prevalence of TPOAb-positive was significantly different between the two groups. Other studies have also shown that elevated TPOAb is predominant in patients with positive thyroid autoimmunity whether in patients with T2DM alone and NAFLD alone, 9,25,29 consistent with our findings. This study found that the prevalence of thyroid autoimmunity in patients with T2DM complicated with NAFLD was 6.6%, which was not statistically significant compared with T 2 DM alone group (3.7%), but it also showed a significant upward trend.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As can be seen from Table 2, the prevalence of thyroid antibodies positive in the T2DM combined NAFLD group was significantly higher than that in the T2DM group alone, and TPOAb positive are more than TGAb-positive patients, the prevalence of TPOAb-positive was significantly different between the two groups. Other studies have also shown that elevated TPOAb is predominant in patients with positive thyroid autoimmunity whether in patients with T2DM alone and NAFLD alone, 9,25,29 consistent with our findings. This study found that the prevalence of thyroid autoimmunity in patients with T2DM complicated with NAFLD was 6.6%, which was not statistically significant compared with T 2 DM alone group (3.7%), but it also showed a significant upward trend.…”
Section: Discussionsupporting
confidence: 93%
“…20 However, it has also been found that there are many people with T2DM complicated with autoimmune thyroid disease, and the intrinsic mechanism may be more complex. Sarfo-Kantanka, O. and Chen, Y. et al reported the presence of serum thyroid autoantibodies in patients with T2DM and NAFLD, respectively, 9,19 but it remains unknown whether thyroid autoimmunity exists in patients with both chronic endocrine diseases and the intrinsic association. However, in recent years there have been reports on the association of thyroid autoimmunity and thyroid cancer, ischemic stroke, cognitive and emotional disorders and adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further discovered that TgAb may be a protective factor for MAFLD in both genders. To our notice, there is only one study by Chen ( 45 ) focusing on the association between thyroid autoantibodies and NAFLD so far. In contrast, the study revealed a positively association between AITD and the prevalence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid disease information of the 10,441 normal people as a control group came from an epidemiological survey conducted by endocrinology department of Shanghai Ninth People's Hospital in east China from 2014 to 2015. The gender, age, TPOAb, TGAb, TSH, FT3, FT4, and B-ultrasound results of these people are all from the epidemiological investigation (16).…”
Section: Methodsmentioning
confidence: 99%